Integrated Landscape Approaches: Definitions, Conceptualizations, Configurations, and Objectives through the Lens of Distributed Leadership Practices - Ndilanha, Edward Gerald; Jaensson, Jan-Erik; Gwahula, Raphael (European Scientific Journal, ESJ, 2025)
While it is widely recognised that integrated landscape approaches are strategic management and leadership strategies used by project team leadership to design, develop, and implement projects within integrated transboundary landscapes and seascapes, it is, however, less clear how they are defined, conceptualised, configured and operationalised to achieve desired outcomes. This study contributes to knowledge by providing a new configuration and conceptualisation of the integrated transboundary landscapes and seascapes conceptual framework; the four principles of integrated landscape approaches - (1) Landscape Partnership, (2) Shared Understanding, (3) Vision and Planning, and (4) Taking Action - need to be seen as strategic management and leadership objectives of the activity systems. To achieve this, the relationship between the four principles of integrated landscape approaches - (1) Landscape Partnership, (2) Shared Understanding, (3)Vision and Planning, and (4) Taking Action - as strategic management and leadership objectives is explored, drawing theoretical foundations from the four widely used distributed leadership practices: engaging, developing, enabling, and empowering. Data were collected through a survey instrument distributed to a sample of 420 participants, followed by statistical analysis using EFA and CFA to validate the model. The findings and implications of the results suggest the existence of a strong relationship between the integrated landscape approaches and the four practices of distributed leadership. It is revealed that (i) they draw from theoretical foundations; (ii) they operate independently of one another; (iii) they exhibit high levels of cross-loading; (iv) they can be integrated into a network of activity systems; (v) they require enactment in a specific order of primacy to function effectively; and (vi) they constitute a normative decision- making framework.